Automated image detection of the main bloodstream stem from CT angiography image. Issue 25 (2016) - Ondraczka, T.; Machacek, Z.; Kubicek, J.; Bryjova, I.; Cerny, M.; Koziorek, J.; Prochazka, V.
Abstract: Purpose of this paper is to design automatized system for detection of main bloodstream stem and to use its output for another processing. System is designed to get image ready for segmentation after using two images, obtained by examination with medical device called computer tomography, using method digital subtraction tomography. The methods for subtraction, normalization and filtration are used as pre-processing. The blood vessels are objects of interest in images, and this is why the designed system separate them from the background. Segmentation methods are used for displaying main bloodstream stem from blood vessels. This output can be used for another applications of larger project. Next applications will be finding blood vessels connected on main blood-stream stem and to separate them, using outputs for verification of therapy success or output that can be used after connection with database for comparison of therapy success in time.